5+3×{2+2×[4+4×(3+3÷3)]-1}-5
Răspunsuri la întrebare
Răspuns de
1
5+3*[2+2*(4+4*4)-1]-5=
5+3*[2+2*20-1]-5=
5+3*(2+40-1)-5=
5+3*41-5=
5+123-5=
=123
5+3*[2+2*20-1]-5=
5+3*(2+40-1)-5=
5+3*41-5=
5+123-5=
=123
Răspuns de
25
5+3×{2+2×[4+4×(3+3÷3)]-1}-5=
5+3×[2+2×(4+4×4)-1]-5=
5+3×[2+2×20-1]-5=
5+3×(2+40-1)-5=
5+3×41-5=
5+123-5=
=123
5+3×[2+2×(4+4×4)-1]-5=
5+3×[2+2×20-1]-5=
5+3×(2+40-1)-5=
5+3×41-5=
5+123-5=
=123
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă